Nomenclature and diagnosis of gluten-related disorders: A position statement by the Italian Association of Hospital Gastroenterologists and Endoscopists (AIGO). Issue 2 (February 2017) - Elli, Luca; Villalta, Danilo; Roncoroni, Leda; Barisani, Donatella; Ferrero, Stefano; Pellegrini, Nicoletta; Bardella, Maria Teresa; Valiante, Flavio; Tomba, Carolina; Carroccio, Antonio; Bellini, Massimo; Soncini, Marco; et al.
Abstract: Background: "Gluten-related disorders" is a term that encompasses different diseases induced by the ingestion of gluten-containing food. Because of their incidence the scientific community has been intensively studying them. Aim: To support gastroenterologists with a correct nomenclature and diagnostic approach to gluten-related disorders in adulthood. Methods: The Italian Association of Hospital Gastroenterologists and Endoscopists (AIGO) commissioned a panel of experts to prepare a position statement clarifying the nomenclature and diagnosis of gluten-related disorders, focusing on those of gastroenterological interest. Each member was assigned a task and levels of evidence/recommendation have been proposed. Results: The panel identified celiac disease, wheat allergy and non-celiac gluten sensitivity as the gluten-related disorders of gastroenterological interest. Celiac disease has an autoimmune nature, wheat allergy is IgE-mediated while the pathogenesis of non-celiac gluten sensitivity is still unknown as is the case of non-IgE mediated allergy. Diagnosis should start with the serological screening for celiac disease and wheat allergy. In case of normal values, the response to a gluten-free diet should be evaluated and a confirmatory blind food challenge carried out. Conclusions: Gluten-related disorders are clinically heterogeneous. Patients should be carefully managed and specific protocols applied for a correct differential diagnosis in gastroenterological setting.